Optimizing components and evaluating technical performance of IR thermographic NDT systems; Proceedings of SPIE; Vol. 9861 : Thermosense: Thermal Infrared Applications XXXVIII - Chulkov A. O. Arseniy Olegovich (Nondestructive Testing and Composites, 2016)
Title screen